Діджиталізація та її вплив на сервісні інновації - Шапошник, А. О. (Право, 2019)
Стаття присвячена дослідженню концепція діджиталізації суспільства, впровадження цифрової економіки та їх вплив на надання інноваційних послуг. Аналізовані різновиди інновацій за типом вигоди або користі, яку вони приносять споживачеві та за рівнем «визначеності» послуги. Розглянуті послуги, які використовують інновацію та послуги, які формують нові ринки. // The article is devoted to the study of the concept of Diabitalization of Society, the introduction of a digital economy and their impact on the provision of innovative services. The varieties of innovations are analyzed by the type of benefits or benefits that they bring the consumer and by the level of "certainty" services. The services that use innovation and services that form new markets are considered.
Keywords: діджиталізація; послуги; інноваційні послуги; інноваційний цикл; diatorization; services; innovative services; innovative cycle